An Optimized In-House Protocol for Cryptococcus neoformans DNA Extraction from Whole Blood: “Comparison of Lysis Buffer and Ox-Bile Methods” - Fredrickson B Wasswa; Kennedy Kassaza; Kirsten Nielsen; Joel Bazira (Journal of Fungi, 2025)
Cryptococcus neoformans (C. neoformans) is a capsulated yeast that enters the body through inhalation and migrates via the bloodstream to the central nervous system, causing cryptococcal meningitis. Diagnosis methods are culture, serology, and India ink staining, which require cerebrospinal fluid (CSF) or whole blood. Molecular methods are used for epidemiological studies and require expensive commercial DNA extraction kits. This study aimed to develop an economical in-house method for extracting C. neoformans DNA from whole blood. C. neoformans cells of varying McFarland standards were spiked into expired blood, then lysed using laboratory-prepared lysis buffer and ox-bile solution, followed by organic DNA extraction. Ordinary PCR targeting the CNAG 04922 gene was performed. To determine the limit of detection, serial dilutions of C. neoformans were made, and DNA extraction was performed on other parts cultured on yeast extract peptone dextrose agar to determine colony-forming units (CFU). The lysis buffer method successfully extracted DNA from as low as the average of 62 CFU in 0.9 mL of expired blood with superior quality and high yield compared to ox-bile. The lysis buffer method yielded higher DNA quality and quantity than ox-bile and detected low concentrations of C. neoformans in expired blood. This method presents a cost-effective alternative for molecular diagnosis in resource-limited settings.
Keywords: : ox-bile; lysis buffer; Cryptococcus neoformans in blood